2021
DOI: 10.3390/mi12091078
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Elshazli et al. Laser Surface Modification of TC21 (α/β) Titanium Alloy Using a Direct Energy Deposition (DED) Process. Micromachines 2021, 12, 739

Abstract: In the original article [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In addition, the new phases in the metal matrix coating (MMC) layers were found to be strongly dependent on the heat input amount. In the research of Elshazli et al, [24] laser cladding was performed by applying different WC percentages with stellite-6 (Co-based alloy) to the surfaces of TC21 titanium alloy. The authors reported that the wear resistance of the deposited layer was significantly improved, as reflected by a decrease in the samples' wear weight loss by 99 pct.…”
mentioning
confidence: 99%
“…In addition, the new phases in the metal matrix coating (MMC) layers were found to be strongly dependent on the heat input amount. In the research of Elshazli et al, [24] laser cladding was performed by applying different WC percentages with stellite-6 (Co-based alloy) to the surfaces of TC21 titanium alloy. The authors reported that the wear resistance of the deposited layer was significantly improved, as reflected by a decrease in the samples' wear weight loss by 99 pct.…”
mentioning
confidence: 99%